EFIKASI DIRI DENGAN KEJADIAN LUKA PADA PASIEN DIABETES MELLITUS TIPE 2 : STUDI KORELASI - Usman Usman (IKesT Muhammadiyah Palembang, 2023)
Introduction:Diabetes Mellitus (DM) is a non-communicable disease that threatens human life. The incidence of DM continues to increase dramatically from year to year. One of the complications that can be caused by DM is Diabetic Foot Ulcer (DFU). Therefore self-efficacy is needed in patients to solve the problems they face and increase the patient's independent efforts in treating it. Aim:To determine the relationship between self-efficacy and the incidence of DFU patients with type 2 DM. Method:Used an analytical observational method with a cross sectional approach. The Diabetes Management Self-Efficacy Scale questionnaire used in this study, while the dependent variable used a wound occurrence checklist. Total samples were 60 patients with purposive sampling technique. The research was conducted at the Kitamura Clinic in Pontianak and at the community setting Punggur Village. Result:The results of data analysis used spearman rank showed that there was a statistically significant relationship with P= 0.00 < 0.05. The variables correlation is high, it is 0.471, and had possitive effect means that if has hight self-efficacy of DM patients,it will be low risk of Diabetic Foot Ulcer. This study indicates that the importance of self-efficacy of patients with DM in order to prevent Diabetic Foot Ulcer.